2019
DOI: 10.33552/appr.2019.01.000527
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Novel Spectro- Chemometric, Chemometric and TLC-Densitometric Methods for Simultaneous Determination of Timolol and Travoprost in their Bulk Powders and Pharmaceutical Formulation

Abstract: This work is licensed under Creative Commons Attribution 4.0 License APPR.MS.ID.000527.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Salem et al [58] established a thin layer chromatography (TLC)-densitometric method for simultaneous determination of a binary mixture of timolol and travoprost without prior separation in their bulk or dosage forms. The separation was carried out on Merck HPTLC aluminum sheets of silica gel 60 F254 using ethyl acetate-methanol-ammonia (5:3:0.5 by volume) as mobile phase.…”
Section: -Tlc Densitometrymentioning
confidence: 99%
See 3 more Smart Citations
“…Salem et al [58] established a thin layer chromatography (TLC)-densitometric method for simultaneous determination of a binary mixture of timolol and travoprost without prior separation in their bulk or dosage forms. The separation was carried out on Merck HPTLC aluminum sheets of silica gel 60 F254 using ethyl acetate-methanol-ammonia (5:3:0.5 by volume) as mobile phase.…”
Section: -Tlc Densitometrymentioning
confidence: 99%
“…The separation was carried out on Merck HPTLC aluminum sheets of silica gel 60 F254 using ethyl acetate-methanol-ammonia (5:3:0.5 by volume) as mobile phase. Detection was done at 274 nm, and linearity was 0.4-50 μg/band for both drugs [58]. Eissa et al [59] suggested a TLC densitometric method for the simultaneous detection of brinzolamide and timolol maleate in pharmaceutical products.…”
Section: -Tlc Densitometrymentioning
confidence: 99%
See 2 more Smart Citations